Digital Experience, Trust, and Enrollment Intention in Islamic Higher Education: An SPSS-Based Study - Dikdik Firman Sidik (Program Pascasarjana UNU Surakarta, 2026)
This study aims to analyze the influence of digital experience on enrollment intention in Islamic Higher Education Institutions with trust as a mediating variable. The research employed a quantitative approach with a cross-sectional survey design. Data were collected from 206 prospective students who were in the process of selecting Islamic Higher Education Institutions in Indonesia through an online questionnaire adapted from validated scales. Data analysis was conducted using SPSS version 26.0 through descriptive statistics, classical assumption testing, multiple regression analysis, and the Sobel mediation test. The results showed that digital experience has a positive and significant effect on trust (β = 0.752, p < 0.001), digital experience has a positive and significant effect on enrollment intention (β = 0.238, p < 0.001), and trust has a positive and significant effect on enrollment intention (β = 0.538, p < 0.001). Furthermore, trust was proven to partially mediate the relationship between digital experience and enrollment intention (indirect effect = 0.397, z = 7.856, p < 0.001). These findings confirm that superior digital experience not only directly drives enrollment intention but also indirectly through trust-building. This study provides theoretical contributions by extending the Technology Acceptance Model in the context of Islamic higher education marketing and offers practical implications for Islamic Higher Education institution administrators to optimize digital platforms and trust-based communication strategies.